2018
DOI: 10.1098/rsos.172376
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-143 and miR-145 in condyloma acuminatum promotes cellular proliferation and inhibits apoptosis by targeting NRAS

Abstract: The expression profile of miRNAs and their function in condyloma acuminatum (CA) remains unknown. In this study, we aimed to detect the effects of miR-143 and miR-145, the most downregulated in CA samples using high-throughput sequencing, on cell proliferation and apoptosis, to determine a novel therapeutic target for CA recurrence. RT-qPCR was used to validate the lower expression of miR-143 and miR-145 in a larger size of CA samples, and the expression of NRAS in CA samples was significantly higher than self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…NRAS was heterogeneously expressed with the expression of both wild type NRAS and NRAS -Q61H observed in RD cells ( Figure S4 ). Moreover, MIR143-3p targets NRAS [ 39 ]. Then, we verified whether CM-MIR143#12 inhibited the expression of NRAS in RD cells.…”
Section: Resultsmentioning
confidence: 99%
“…NRAS was heterogeneously expressed with the expression of both wild type NRAS and NRAS -Q61H observed in RD cells ( Figure S4 ). Moreover, MIR143-3p targets NRAS [ 39 ]. Then, we verified whether CM-MIR143#12 inhibited the expression of NRAS in RD cells.…”
Section: Resultsmentioning
confidence: 99%
“…These innovations will further propel the implementation and acceptance of organotypic human skin models as excellent alternatives or superior experimental models to the traditional use of animals in biomedical research. J o u r n a l P r e -p r o o f (Hainzl et al, 2017) 28800953 RDEB primary keratinocytes gene correction Xfect Cationic vector SpCas9 HDR puromycin and b (Kocher et al, 2017) 28888469 Adult primary keratinocytes protein knock-out Electroporation Plasmid vector SpCas9 NHEJ blasticidin 29287762 Adult primary keratinocytes protein knock-out lentiCRISPR v2 Lentivirus SpCas9 NHEJ puromycin (Fenini Gabriele et al, 2018) 30096351 Adult primary keratinocytes protein knockout lentiCRISPR v2 Lentivirus SpCas9 NHEJ puromycin (Izmiryan et al, 2018) 30195791 RDEB primary keratinocytes gene correction IDLV Lentivirus SpCas9 HDR none (Liu et al, 2018) 30225000 Adult primary keratinocytes protein knock-out FuGene HD Cationic vector SpCas9 NHEJ puromycin (Slivka et al, 2019) 30938974 Adult primary keratinocytes CRISPR screen lentiCRISPR v2 Lentivirus SpCas9 NHEJ puromycin and b (Herter et al, 2019) 30594489 Adult primary keratinocytes gene activation Lipofectamine 2000 Cationic vector dCas9 n/a FACS (Jozic et al, 2019) 31409528 Adult primary keratinocytes protein knock-out FuGene HD Cationic vector SpCas9 NHEJ puromycin (Grossi et al, 2020) 31502220 (Webber et al, 2016) 28250968 Induced pluripotent stem cells gene correction Electroporation Plasmid vector hCas9 HDR puromycin (Shinkuma et al, 2016) 27143720 Induced pluripotent stem cells gene correction Electroporation Plasmid vector SpCas9 NHEJ FACS (Jackow et al, 2019) 31818947 Induced pluripotent stem cells gene correction Electroporation RNP complex SpCas9 HDR FACS (Itoh et al, 2020) 32376152 Induced pluripotent stem cells gene correction Electroporation RNP complex SpCas9 HDR puromycin Abbreviations: E6/E7: papillomavirus E6/E7 protein; FACS: fluorescence-activated cell sorting; HDR: homology-directed repair; IDLV: integrase-deficient lentiviral particles; JEB: junctional epidermolysis bullosa; NHEJ: non-homologous end joining; RDEB: recessive dystrophic epidermolysis bullosa; RNP: ribonucleoprotein complex J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Researches have shown that the dysregulated miRNAs, such as miR-26a and miR-145 are involved with the pathogenesis of CA [6,7]. However, the speci c mechanism of miRNA in CA remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%